اسلامی تاریخی ناول نگاروں کا ادبی مقام و مرتبہ: نسیم حجازی کا خصوصی مطالعہLiterary Status of Islamic Historical Novelists: A Special Study of Naseem Hijazi (Al-Qamar, 2021)
Naseem Hijazi is generally known as an Islamic historical novelist. It is true that he has written fourteen Islamic historical novels. Addition to that he has also written two biographical novels. He is a writer of four books on irony and humor namely Safaid Jazeera, Saw Saal Baad, Saqafat ki Talash and Porus kay Hathi. Nasim has written a travel book named Pakistan sy Dayar e Haram Tak too. Thus it is rightly said that he  is  much more a than mere islamic historical  novelist. He is also a successful wit writer and a "Safarnama" writer. In addition to all that, Nasim Hijazi has been a great journalist and very smart political thinker  of his times. So I have made an effort to highlight his literary position among Urdu writers so that the readers may know enough about his dignified position in Urdu literature. The effort is purely research based and justified. No polarization and praising tools are used to show Nasim Hijazi a great writer in this research article.
Keywords: Nasim Hijazi; Islamic Historical Novel; biographical novels; irony and satire; political thinker; Journalist; Safarnama Nigaar